Guide to Computer Network Security - Kizza, Joseph Migga (Springer, 2015)
The second edition of this book came out barely 2 years ago and we are again in need of a new and improved third edition. This rapid turnaround of editions of a successful book like this is indicative of the rapidly changing technology landscape. To keep a promise we made to our readers in the first edition of keeping the book materials as up to date as possible, we have now embarked on this third edition. First, recall that in the second edition, we introduced to the reader the concept of a changing traditional Computer Network as we knew it when the first edition of this book came out. That network with a nicely “demarcated” and heavily defended perimeter wall and well guarded access points has been going into a transformation as a result of new technologies. Changes have occurred, as we pointed out in the second edition, within and outside the network we call the “traditional computer network”, at the server and most importantly at the boundaries. A virtualized and elastic network with rapid extensions at will is taking its place to meet the growing needs of users. The new technologies driving this change, for now, are system resource virtualization, the evolving cloud computing models and a growing and unpredictable mobile computing technology creating platforms that demand new extensions, on the fly and at will, to the traditional computer network...